Soybean Response to Sulfur in Typic Arguidolls of Southwestern Uruguay - García Lamothe, Adriana; Quincke, J. Andrés; Sawchik, Jorge (Agrociencia Uruguay, 2017)
Sulfur (S) is an essential nutrient, necessary to maintain crop productivity. Agriculture intensification in Uruguay has increased the risk of nutrient deficiencies in soils. The goal of this study was to explore soybean response to S application and the feasibility of using soil sulfate concentration, and potentially mineralizable nitrogen (PMN) as indicators of S-availability. Thirteen field trials were conducted during six growing seasons (2007 to 2012) at the Experimental Station La Estanzuela, Colonia, on typical Argiudols of the area. Sulfur as gypsum was applied at rates of 0, 15, 30 and 45 kg S ha-1, with treatments allocated in four complete randomized blocks. Variation in precipitation amount and distribution affected soybean grain yield across the years and thereby fertilization response. Only in two trials yield responses were statistically significant, with increases that amounted about 15 %. For the soils studied, positive responses to S would be likely when soil sulfate concentration is less than 5 mg kg-1 at planting. In such cases yield increases ranged between 204 and 467 kg ha-1. When soil sulfate test is higher, odds for yield increases from applied S are low, with chances of observing negative responses, too. No relation between PMN and yield response could be found.